KUALITAS PELAYANAN BUS RAPID TRANSIT (BRT) TRANS PATRIOT KOTA BEKASI - Olivia Priskila Polem; Ari Subowo; Augustin Rina Herawati (Jurusan Administrasi Publik, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Diponegoro, 2023)
Transportation is one of the main aspects in realizing the welfare of the community) in Indonesia there are three transportation sectors namely, air transportation, water transportation, land transportation. As a very important means in supporting the success of development and supporting community economic activities, services in the transportation sector have a role in the attention because it affects the formation of the city. As a form of public service innovation in the transportation sector, the Bekasi City Government is in collaboration with Patriot Partners as a regional company owned by the Bekasi City Government to form Trans Rapid Trans (BRT) Trans Patriot. Bus Rapid Trans Patriot is an increase in services in the field of public transportation in Bekasi City with the aim of facilitating the accessibility of the people in Bekasi City by creating a comfortable, safe and easy public transportation. This study aims to analyze the quality of Trans Rapid Transit (BRT) of Bekasi City Transit (BRT) and find out the factors related to the quality of Trans Rapid Transit Service (BRT) Trans Patriot Bekasi City. This study uses a qualitative method with a descriptive type with informant selection technique, Purposive sampling and to test the validity of data using source triangulation. The results showed that the quality of the Transit Transit (BRT) of Bekasi City Rapid Transit (BRT) services was not good.